MENGOPTIMALKAN PEMBELAJARAN BERDIFERENSIASI BAGI SISWA TUNARUNGU DI SEKOLAH DASAR - A Zulkarnain Ali; Ade Irma Novianti; Selasi Priatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze and optimize differentiated learning strategies for deaf students at the elementary school level. Inclusive education requires responsive learning adaptations to the needs of all students, including those with hearing impairments. This study uses a qualitative approach with a descriptive analytical method, which examines learning practices that have been implemented, the gap between theory and practice, and formulates optimal strategies based on differentiation theory (Tomlinson) and Universal Design for Learning (UDL). The results of the study indicate that existing learning practices still do not fully meet the needs of deaf students, especially in terms of communication, visual media, and appropriate assessment. Learning strategies that include the use of visual media, sign language training, collaboration with accompanying teachers, and the use of technology have been proven to increase the participation and learning outcomes of deaf students. This study recommends the implementation of planned and collaborative differentiated learning as the key to the success of inclusive education in elementary schools.